The humanized DRAGA mouse (HLA-A2. HLA-DR4. RAG1 KO. IL-2R g c KO. NOD) establishes inducible and transmissible models for influenza type A infections - Mirian Mendoza; Devi Gunasekera; Kathleen P. Pratt; Qi Qiu; Sofia Casares; Teodor-D. Brumeanu (Taylor & Francis Group, 2020)
We have engineered a Human Immune System (HIS)-reconstituted mouse strain (DRAGA mouse: HLA-A2. HLA-DR4. Rag1 KO. IL-2Rγc KO. NOD) in which the murine immune system has been replaced by a long-term, functional HIS via infusion of CD34+ hematopoietic stem cells (HSC) from cord blood. Herein, we report that the DRAGA mice can sustain inducible and transmissible H1N1 and H3N2 influenza A viral (IAV) infections. DRAGA female mice were significantly more resilient than the males to the H3N2/Aichi infection, but not to H3N2/Hong Kong, H3N2/Victoria, or H1N1/PR8 sub-lethal infections. Consistently associated with large pulmonary hemorrhagic areas, both human and murine Factor 8 mRNA transcripts were undetectable in the damaged lung tissues but not in livers of DRAGA mice advancing to severe H1N1/PR8 infection. Infected DRAGA mice mounted a neutralizing anti-viral antibody response and developed lung-resident CD103 T cells. These results indicate that the DRAGA mouse model for IAV infections can more closely approximate the human lung pathology and anti-viral immune responses compared to non-HIS mice. This mouse model may also allow further investigations into gender-based resilience to IAV infections, and may potentially be used to evaluate the efficacy of IAV vaccine regimens for humans.